Internalized HIV/AIDS-related Stigma in a Sample of HIV-positive People in Bangladesh - Hasan, Md Tanvir; Nath, Samir Ranjan; Khan, Nabilah S; Akram, Owasim; Gomes, Tony Michael (Journal of Health, Population and Nutrition, 2012)
Internalized stigma among people living with HIV/AIDS (PLHA) is prevalent in Bangladesh. A better understanding of the effects of stigma on PLHA is required to reduce this and to minimize its harmful effects. This study employed a quantitative approach by conducting a survey with an aim to know the prevalence of internalized stigma and to identify the factors associated with internalized stigma among a sample of 238 PLHA (male=152 and female=86) in Bangladesh. The findings suggest that there is a significant difference between groups with the low- and the high-internalized HIV/AIDS stigma in terms of both age and gender. The prevalence of internalized stigma varied according to the poverty status of PLHA. An exploratory factor analysis (EFA) found 10 of 15 items loaded highly on the three factors labelled self-acceptance, self-exclusion, and social withdrawal. About 68% of the PLHA felt ashamed, and 54% felt guilty because of their HIV status. More than half (87.5% male and 19.8% female) of the PLHA blamed themselves for their HIV status while many of them (38.2% male and 8.1% female) felt that they should be punished. The male PLHA more frequently chose to withdraw themselves from family and social gatherings compared to the female PLHA. They also experienced a higher level of internalized stigma compared to the female PLHA. The results suggest that the prevalence of internalized stigma is high in Bangladesh, and much needs to be done by different organizations working for and with the PLHA to reduce internalized stigma among this vulnerable group. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11272 J HEALTH POPUL NUTR 2012 Mar;30(1):22-30